ASSESSING VALIDITY AND RELIABILITY OF PHYSICAL AND PSYCHOLOGICAL VIOLENCE VICTIMIZATION INSTRUMENT AMONG ADOLESCENTS IN DATING RELATIONSHIPS - Suci Musvita Ayu; Erni Gustina; Liena Sofiana; Thoharoh Halimatusa’diyah; Soeharto Soeharto; Moh. Irma Sukarelawan; Ratu Matahari; Septian Emma Dwi Jatmika (IAKMI South Tangerang Branch, 2024)
Background: Couple victimization among adolescents has an impact on their physical and psychology. The objectives of this study were to evaluate the validity and reliability of a physical and psychological violence scale among dating adolescents. Methods: A total of 294 students participated in this study. The participants were chosen using a basic random sampling approach. The validity of the proposed scale was assessed using expert judgement, t-values, and Standardized Loading Factors (SLFs) using Confirmatory Factor Analysis. The reliability of each construct was determined using the Construct Reliability (CR) value. The acquired data satisfied the criterion for goodness-of-fit based on Confirmatory Factor Analysis. The experts deemed a total of 37 items valid. Results: The Confirmatory Factor Analysis demonstrates that the 32-item scale measuring victims of physical and psychological violence meets the criteria for validity and reliability. The t-values range from 6.41 to 17.87, the standardized loading factor ranges from 0.38 to 0.85 confirming construct validity achieved, and the construct reliability ranges from 0.89 to 0.93 showing all construct or latent factors achieving acceptable reliability criteria. Conclusion: Victims of physical and psychological assault met the criteria for being valid and reliable.